PERAN CSR (CORPORATE SOCIAL RESPONSIBILITY) “SAVE THE CHILDREN (STC)” DALAM MENDUKUNG PEMBIAYAAN PENDIDIKAN BERKELANJUTAN DI SMPN 3 RANCAEKEK: DI SMPN 3 RANCAEKEK - Helmawati, Helmawati; Suherman, Maman; Mulhima Prihatini, Ima; Komalasari, Kokom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays a vital role in sustainable development, and the business world through CSR (Corporate Social Responsibility) programs can expand access, improve quality, and encourage empowerment through leadership development and education. The purpose of this study is to obtain information or an overview and analyze the role of CSR (Corporate Social Responsibility)